EFFECTIVENESS OF COMPOST EXTRACT INDUCING SYSTEMIC RESISTANCE IN CIGAR TOBACCO PLANT AGAINST Cucumber Mosaic Virus (CMV) - Abdullah Umar; Wiwiek Sri Wahyuni (Widyariset, 2013)
Tobacco is a highly valuable commodity and Cucumber mmosaic vvirus (CMV) is an economically important disease. This study was aimed to determine the effectiveness of compost extract inducing systemic resistance in cigar tobacco against CMV. The experiment was arranged in a randomized block design (RBD) with two factors (5/K x2/V). K factor consisted of five types of three kinds of compost extract, Pseudomonas putida and control, while factor V consisted of 2 types of with or without virus inoculation. Each treatment was repeated 5 times. Its effectiveness was assessed by observing severity of the disease at 24, 27, 31, 36, 40, and 44 days after virus inoculation. The result showed that application of compost extract or P. putida Pf-20 on 15 days before inoculation of CMV could induce the systemic resistance of cigar tobacco and extended to the period of incubation up to 22 days. Rice straw compost extract was more effective than leaf litter compost extract or coffee husks. However, the indication effectiveness of those three extract were lower than P. putida.